The role of leadership in promoting peace and order a case study of the regime of Mayor Rodrigo Duterte in Davao City (1988-2004). - Sembrano, Jennylou
With the passage of the 1991 Local Government Code, there was a transfer of power from the national to the local government. In this regard, local leaders are given more authority in governing their respective communities. Political leadership in this case becomes more critical. In the case of political instability, local leaders are compelled to use their ingenuity, audacity and willingness to address crises situations., This is a case study of Davao Mayor Rodrigo Duterte's strategies to improve the peace and order situation of Davao City. Through interviews and newspaper archival research, this study sought to examine the controversial dimensions of his strategies; The changes in the peace and order situation in Davao City before and during his terms; and the local constituent's perception on the peace and order measures taken by him. It also examines the relationship among the local mayor, the PNP and the military with regards to their efforts in achieving peace and order. This study also seeks to explain the relationship between the leadership of the local chief executive, the establishment of peace and order, and the legitimacy of his leadership. Mayor Duterte - with his distinctive styles and strategies in promoting peace and order - is highly successful in combating insurgency related crimes and street crimes such as theft, robbery, drugs, etc. Although he is alleged to have strategy that questions human right violation (the notorious Davao Death Squad), there was no public outcry and he was well accepted by his constituents - as shown by the number of terms he was re-elected into office and the massive votes he obtained during the past election years.